Anticancer 5‐arylidene‐2‐(4‐hydroxyphenyl)aminothiazol‐4(5H)‐ones as tubulin inhibitors. Issue 12 (15th September 2022) - Rehulka, Jiri; Subtelna, Ivanna; Kryshchyshyn‐Dylevych, Anna; Cherniienko, Alina; Ivanova, Aleksandra; Matveieva, Mariia; Polishchuk, Pavel; Gurska, Sona; Hajduch, Marian; Zagrijtschuk, Oleh; Dzubak, Petr; Lesyk, Roman
Abstract: Studying the anticancer activity of 5‐arylidene‐2‐(4‐hydroxyphenyl)aminothiazol‐4(5 H )‐ones towards cell lines of different cancer types allowed the identification of hit‐compounds inhibiting the growth of daunorubicin‐ (CEM‐DNR, IC50  = 0.32–1.28 µM) and paclitaxel‐resistant (K562‐TAX, IC50  = 0.21–1.23 µM) cell lines, with favorable therapeutic indexes. The studied compounds induced apoptosis and cellular proliferation in treated CCRF‐CEM cells. The hit compounds were shown to induce mitotic arrest by interacting with tubulin, inhibiting its polymerization by binding to the colchicine binding site. Abstract : New 5‐arylidene‐2‐(4‐hydroxyphenyl)aminothiazol‐4(5 H )‐ones with submicromolar cytotoxic activity (IC50 0.10–2.12 µM) and favorable therapeutic index towards CCRF‐CEM, CEM‐DNR, HCT‐116, HCT116p53−/−, K‐562, K562‐TAX, and U2OS cells were identified. Hit compounds 3, 10, and 12 induced mitotic arrest by interacting with microtubules, inhibiting their polymerization by binding to the colchicine binding site.